2015
DOI: 10.1108/dat-11-2014-0039
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the service provision for ethnic minorities in Islington in the treatment of substance misuse

Abstract: Purpose – The purpose of this paper is to illustrate how local drug services use their senior staff to respond to emerging ethnic groups presenting to treatment using flexible thinking and innovative processes. Design/methodology/approach – The methodology was a case study design that used a semi-structured questionnaire that looked at two drug services and their staff’s influence on service delivery in different boroughs of east London.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Ethnic minorities are not homogenous; coupled with a lack of reliable and valid data available in the UK on substance use across ethnicities, it is inherently difficult to develop tailored support packages for such diverse young people (Wanigaratne et al , 2003). As mentioned by some of our participants, across drug treatment services there are “new” ethnic minority populations such as Eastern Europeans who are now presenting more frequently to services that are not prepared to meet their needs for culturally appropriate treatment approaches (Fernandez, 2015). Some practitioners also perceived family norms to impede engagement of young people, perhaps inadvertently using cultural stereotypes to explain why they struggle to effectively intervene with some minority groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ethnic minorities are not homogenous; coupled with a lack of reliable and valid data available in the UK on substance use across ethnicities, it is inherently difficult to develop tailored support packages for such diverse young people (Wanigaratne et al , 2003). As mentioned by some of our participants, across drug treatment services there are “new” ethnic minority populations such as Eastern Europeans who are now presenting more frequently to services that are not prepared to meet their needs for culturally appropriate treatment approaches (Fernandez, 2015). Some practitioners also perceived family norms to impede engagement of young people, perhaps inadvertently using cultural stereotypes to explain why they struggle to effectively intervene with some minority groups.…”
Section: Discussionmentioning
confidence: 99%
“…Within the research on BAME adult use of substance use services, perceptions of a lack of cultural diversity and sensitivity among service providers is seen to act as a barrier to help-seeking (see Fountain, 2009). While also citing cultural stigma as a further barrier, this research found that many from BAME communities find services difficult to engage with individually and have a desire for more family involvement in their treatment, an approach which was not usually made available to them (Fountain, 2009; Fernandez, 2015). This research does not differentiate between older and younger generations however, and it is not clear if, or by how much, young people’s preferences for substance use intervention differ from those of adults.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation